Budaya Indonesia PERAN BIPA DALAM MEMPERKENALKAN BUDAYA INDONESIA: Budaya Indonesia - Indah Hapsari; Khaerunnisa (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
The function of the Indonesian language is as a symbol of national pride, national identity, as a means of communication between citizens, regions and cultures, as well as a means of unifying tribes, cultures, and languages. There are several efforts made by the Indonesian government in internationalizing the Indonesian language, including: developing the Indonesian language both at home and abroad and protecting the Indonesian language through several journals that are recognized by the Indonesian government. BIPA is Indonesian language learning whose subjects are foreign speakers. BIPA is seen more as a learning factor. The author uses qualitative research methods with object observation models. Data collection techniques are carried out by emphasizing the meaning of generalization. By watching Youtube shows that contain elements of Indonesian culture, several YouTube channels show learning videos that introduce Indonesian culture, be it dance, batik cloth, to pencak silat and an introduction to culture in/in Indonesia. Keywords: BIPA, Culture, Indonesia